Thermodynamic measurement of the sound velocity of a Bose gas across the transition to Bose–Einstein condensation. (10th May 2018) - Fritsch, A R; Tavares, P E S; Vivanco, F A J; Telles, G D; Bagnato, V S; Henn, E A L
Abstract: We present an alternative method for determining the sound velocity in atomic Bose–Einstein condensates, based on thermodynamic global variables. The total number of trapped atoms was as a function of temperature carefully studied across the phase transition, at constant volume. It allowed us to evaluate the sound velocity resulting in consistent values from the quantum to classical regime, in good agreement with previous results found in literature. We also provide some insight about the dominant sound mode (thermal or superfluid) across a wide temperature range.